USE OF FACEBOOK AS AN EDUCATIONAL TOOL - Ngoyi, Luka; Siuluta, Mwasile Niza; Muwamba, Jerry; Banda, Daliso; Hatilima, Jasper; Ngoyi, Abraham; Mpanga, Shadreck (IJRDO-Journal of Applied Science, 2015)
Technology is ubiquitous, embracing almost every part of our lives, our communities and our homes. In the field of education technology doesn’t have a secondary role in the sole process of knowledge transferring especially because technology is becoming increasingly integrated into the lives of learners of all ages and groups. In particular of this technology is the use of Facebook as an education tool. Originally designed for college students in the United States in 2004, Facebook was created as a social networking website. Facebook later expanded to different educational settings. Facebook allows each user to create a profile, updating it with personal information such as home address, mobile phone number, interesting religious views and also allows people to form groups and post pictures. Today with approximately 800 million subscribers worldwide (according to www.internetworldstats.com), Facebook now has a diverse community of users at all levels of education and areas of society including companies and universities. This number of users all around the globe makes Facebook the most used social network out there. This has made Facebook to be integrated into the way teachers, lecturers and professors teach and administer courses. But like always, the use of Facebook as educational tool has been received with mixed feelings, concerns related to privacy and anxiety in the interaction with professors in this environment, a belief that doesn’t serve an academic purpose and the opinion that facility should simply avoid “education appropriation” these backstage social space have been expressed. Yet other people have supported the notion of using Facebook as an education tool, as survey worldwide has shown